Local Entrepreneurs Involvement in the Procurement of Goods and Services by the Regional Government (Case Study: Construction Service Business Entities in Banten Province) - Romani, Ahmad; Priyambodo, Bambang; Mardiaman, Mardiaman; Simanjuntak, Manlian Ronald A.; Ernamaiyanti, Ernamaiyanti (Universitas Ibn Khaldun, 2026)
The Banten Provincial Government continues to encourage the involvement of local business actors in procurement of goods and services. This is an effort to encourage job opportunities and economic equality in Banten Province. In 2024, the construction business sector will contribute 11.69 percent to the Banten Province economy. The objectives of this study are: 1) To analyze the distribution of local entrepreneurs' involvement in construction and consulting projects in Banten Province. 2). To determine the level of local entrepreneurs' involvement in construction and consulting projects in Banten Province. 3). constraints that influence the involvement of local entrepreneurs in construction services & consulting services projects in Banten Province. The research method is literature study and in-depth interviews with purposive sampling. The research location is Banten Province. Data analysis is descriptive analysis and the relative importance index (RII) calculation method. Construction Service Business Entities (BUJK) in Banten Province have 2,261 BUJK. The distribution of local business involvement in construction projects is generally concentrated in Tangerang Regency, namely 607 BUJK or 26.847%. Contractor services in Banten Province are 92.26% and Consultant services are 7.74%, where the amount varies in each Regency/City. The level of involvement of local business actors in Banten Province in construction projects is 70.01%. Meanwhile, the involvement of local consultant entrepreneurs is 29.99%. The obstacle for local entrepreneurs not being able to get involved in their own business environment (company domicile) is 60.4% because the work is only controlled by certain individuals and 18.9% stated that local entrepreneurs lack the finances to carry out government projects.